Mao's China. Party reform documents, 1942-44. Transl. and introd. by B. Compton. [With contribs of Mao Tse-Tung, Ch'en Yün, Liu Shao-Ch'i and J. Stalin (Ps. of I.V. Džugašvili)] (University of Washington Press, 1966)
University of Washington publications on Asia.